2023
DOI: 10.1101/2023.09.27.559752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular and network disruptions in neurodevelopment uncovered by single cell transcriptomics analysis ofCHD8heterozygous cerebral organoids

Maider Astorkia,
Yang Liu,
Erika M. Pedrosa
et al.

Abstract: About 100 genes have been associated with significantly increased risks of autism spectrum disorders (ASD) with an estimate of ∼1000 genes that may be involved. The new challenge now is to investigate the molecular and cellular functions of these genes during neural and brain development, and then even more challenging, to link the altered molecular and cellular phenotypes to the ASD clinical manifestations. In this study, we use single cell RNA-seq analysis to study one of the top risk gene,CHD8, in cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Therefore, CHD8 knockout induced an activation of microglia. In a separate study of CHD8 knockdown in human cerebral organoids, Astorkia et al demonstrated that CDH8 reduction leads to impaired neuronal-glial communication 63 . The decrease in number of microglia, in comparison to the activation of microglia, is more difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CHD8 knockout induced an activation of microglia. In a separate study of CHD8 knockdown in human cerebral organoids, Astorkia et al demonstrated that CDH8 reduction leads to impaired neuronal-glial communication 63 . The decrease in number of microglia, in comparison to the activation of microglia, is more difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%